Answer:
(See attached graph)
Explanation:
To solve a second-order homogeneous differential equation, we need to substitute each term with the auxiliary equation
where the values of
are the roots:
![y''-6y'+9y=0\\\\m^2-6m+9=0\\\\(m-3)^2=0\\\\m-3=0\\\\m=3](https://img.qammunity.org/2023/formulas/mathematics/college/no6zekhv1slr3twj1n34mpko2v5u6zczy5.png)
Since the values of
are equal real roots, then the general solution is
.
Thus, the general solution for our given differential equation is
.
To account for both initial conditions, take the derivative of
, thus,
![y'(x)=3C_1e^(3x)+C_2e^(3x)+3C_2xe^(3x)](https://img.qammunity.org/2023/formulas/mathematics/college/s0armh0lnl5ft1dt503k0j6btlbf0f9db3.png)
Now, we can create our system of equations given our initial conditions:
![y(x)=C_1e^(3x)+C_2xe^(3x)\\ \\y(0)=C_1e^(3(0))+(C_2)/(6)(0)e^(3(0))=0\\ \\C_1=0](https://img.qammunity.org/2023/formulas/mathematics/college/36fep8y606nymnsm7dax6gb3hbce7ink7y.png)
![y'(x)=3C_1e^(3x)+C_2e^(3x)+3C_2xe^(3x)\\\\y'(0)=3C_1e^(3(0))+C_2e^(3(0))+3C_2(0)e^(3(0))=2\\\\3C_1+C_2=2](https://img.qammunity.org/2023/formulas/mathematics/college/q2hwd3aalikkppcvjjw7nl26btucaxse4r.png)
We then solve the system of equations, which becomes easy since we already know that
:
![3C_1+C_2=2\\\\3(0)+C_2=2\\\\C_2=2](https://img.qammunity.org/2023/formulas/mathematics/college/g40vk26rmficl7mey0zj9c8fsv7e7x5tag.png)
Thus, our final solution is:
![y(x)=C_1e^(3x)+C_2xe^(3x)\\\\y(x)=2xe^(3x)](https://img.qammunity.org/2023/formulas/mathematics/college/70xdcq5053yvmvi9dhr55m8pxn0un8do6u.png)